Linear chain of weakly coupled defects in a three-dimensional phononic crystal: A model acoustic waveguide - R. Sainidou; N. Stefanou; A. Modinos (Physical Review B, 2006)
We discuss acoustic waveguiding through weakly coupled defects along a line in a three-dimensional phononic crystal which possesses an absolute frequency gap. A chain of appropriately chosen defect cells induces modes of the elastic field over a narrow band of frequencies within the gap. We introduce a model of this band in the manner of a tight-binding description of defect bands in semiconductors and demonstrate the applicability of this model through a specific example of phononic crystal: a bubbly liquid. This allows an exact, practically analytic solution and a deeper physical insight into the processes involved.